The Determinants of Commercial Bank Profitability in Canada - LI, Ranran (2019)
This dissertation uses average return on equity (ROAE), the average return on assets (ROAA) and net interest margin (NIM) as an indicator, examines the bank-specific factors and the influence of macroeconomic factors on bank profitability by Canadian Banks in 2011-2018, aimed to explore the underlying determinant of Canadian Banks profits, and tries to find out the relationship between bank profitability and its important determinants. Meanwhile, in order to improve the competitiveness of Banks, this paper combines the important determinants with the risk management framework. The results show that cost efficiency and liquidity are the most important and significant factors in determining bank profitability; Macroeconomic factors, including GDP growth rate and inflation rate, have no significant impact on profitability. The proof of the importance of bank-specific factors provides further enlightenment for the practice of bank risk management.